The structure and function of enzimes - Bernhard, Sdney A. (Biology Teaching monogaph series, 1968)
The physicalo forces of interaction between atoms and molecules.--Chemical bonds and the structure of proteins.--Enzime kinetics and formal models of catalysis.--The anatomy of enzymes.--Mechanistic pathways and models of enzyme catalysis.--Coenzimes and cofactors: enzyme models and mechanisns.--Enzyme catalysis: especific examples